How to enhance the stability of locking plate fixation of proximal humerus fractures? An overview of current biomechanical and clinical data. Issue 7 (July 2015) - Schliemann, Benedikt; Wähnert, Dirk; Theisen, Christina; Herbort, Mirco; Kösters, Clemens; Raschke, Michael J.; Weimann, Andre
Abstract Background The complication rate after locking plate fixation of proximal humerus fractures is high. In addition to low bone mineral density, a lack of medial support has been identified as one of the most important factors accounting for mechanical instability. As a result of the high failure rate, different strategies have been developed to enhance the mechanical stability of locking plate fixation of proximal humerus fractures. The aim of the present article is to give an overview of the current biomechanical and clinical studies that focus on how to increase the stability of locking plate fixation of proximal humerus fractures. Methods A comprehensive search of the Medline databases using specific search terms with regard to the stability of locking plate fixation of proximal humerus fractures was performed. After screening of the articles for eligibility, they were subdivided according to clinical and biomechanical aspects. Results Medial support screws, filling of bone voids and screw-tip augmentation with bone cement as well as the application of bone grafts are currently the most frequently assessed and performed methods. Although the evidence is weak, all of the mentioned strategies appear to have a positive effect on achieving and maintaining a stable reduction even of complex fractures. Conclusion Further clinical studies with a higher number of patients and a higher level of evidence are required to develop a standardised treatment algorithm with regard to cement augmentation and bone grafting. Although these measures are likely to have a stabilising effect on locking plate fixation, its general use cannot be fully recommended yet.